2009
DOI: 10.1371/journal.pone.0007308
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses of Pulmonary Epithelial Cells to Burkholderia pseudomallei Infection

Abstract: Background Burkholderia pseudomallei, a facultative intracellular pathogen, causes systemic infection in humans with high mortality especially when infection occurs through an infectious aerosol. Previous studies indicated that the epithelial cells in the lung are an active participant in host immunity. In this study, we aimed to investigate the innate immune responses of lung epithelial cells against B. pseudomallei.Methodology and Principal FindingsUsing a murine lung epithelial cell line, primary lung epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 46 publications
(53 reference statements)
3
37
0
Order By: Relevance
“…Since pangolins may have intrinsically weak mucosal immunity, Burkholderia spp. might easily infect the lung by penetrating lung epithelial cells and the brain by penetrating nasal mucosa and migrating to the brain through olfactory nerves, which has previously been shown with other Burkholderia (Owen et al 2009;Sim et al 2009;Taylor et al 2010;Dando et al 2014;St John et al 2014). Furthermore, captive pangolins are prone to frequently fatal gastrointestinal disease, pneumonia, and skin maladies (Clark et al 2008;Hua et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Since pangolins may have intrinsically weak mucosal immunity, Burkholderia spp. might easily infect the lung by penetrating lung epithelial cells and the brain by penetrating nasal mucosa and migrating to the brain through olfactory nerves, which has previously been shown with other Burkholderia (Owen et al 2009;Sim et al 2009;Taylor et al 2010;Dando et al 2014;St John et al 2014). Furthermore, captive pangolins are prone to frequently fatal gastrointestinal disease, pneumonia, and skin maladies (Clark et al 2008;Hua et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Thus it is reasonable to conclude that as multiple TLRs are subject to stimulation by BP , but not BM , this likely contributed to the vigorous innate immune responses (e.g., cytokine secretion) induced by macrophages and ATII cells in the early stages of infection. Sim et al (2009) showed that primary murine epithelial lung cells both in vitro and in vivo secrete significant levels of pro-inflammatory cytokines in response to BP . Our findings, as well as others (Stevens and Galyov, 2004; Sim et al, 2009), resemble the clinical situation of acute melioidosis in that this disease can lead to induction of pro-inflammatory cytokines with high levels of cytokine secretion, leading to poorer prognosis for infected patients (Simpson et al, 2000; Cheng et al, 2007; Wiersinga et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sim et al (2009) showed that primary murine epithelial lung cells both in vitro and in vivo secrete significant levels of pro-inflammatory cytokines in response to BP . Our findings, as well as others (Stevens and Galyov, 2004; Sim et al, 2009), resemble the clinical situation of acute melioidosis in that this disease can lead to induction of pro-inflammatory cytokines with high levels of cytokine secretion, leading to poorer prognosis for infected patients (Simpson et al, 2000; Cheng et al, 2007; Wiersinga et al, 2007). Alternatively, and very interestingly, BM stimulated minimal cytokine secretion from macrophages and ATII cells in the initial infection stage but stimulated the secretion of pro-inflammatory suppressor, IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of normal lung cells from mice was done as previously described (18,19). Lung tissue was separated and flushed with 10 mL of 1% of penicillin-streptomycin in PBS.…”
Section: Preparation Of Normal Lung Cells From Mousementioning
confidence: 99%